Asupan Cairan dan Aktivitas Fisik dengan Kejadian Dehidrasi pada Mahasiswa Universitas Nasional Jakarta - Maya Anggraeni; Adhila Fayasari (Sarana Ilmu Indonesia (salnesia), 2020)
Dehydration is not only caused by loss of body fluids, but is also influenced by physical activity and adequate fluid consumption. Students carry out various kinds of activities, so that the level of fluid consumption from drinks in students varies. This study aimed to analyze the relationship between fluid intake and physical activity with the incidence of dehydration. This study used a cross sectional study design with 184 male students as subjects at the National University. Data were taken in the form of characteristics, smoking habits, fluid intake (amount and type), as well as physical activity and dehydration conditions. The prevalence of dehydration found among students at the National University of Jakarta was 36,4%. The average amount of fluids consumed by the National University students was 2346,49 ± 1142,05 SD. There was a significant relationship between the amount of fluids consumed and dehydrated conditions (p 0,000), and there was a significant relationship between physical activity and dehydration conditions (p 0,026). There were significant difference in the average fluid intake consumed and physical activity with dehydrated conditions.